Off- to in-season body composition adaptations in elite male and female endurance and power event athletics competitors: an observational study - Pettersson, S.; Kalén, A.; Gustafsson, M.; Grau, S.; Caspers, A. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background Monitoring elite athletes` body composition (BC) is vital for health and optimizing performance in sports emphasizing leanness, such as athletics. This study aims to investigate and compare sex- and event-specific off-to in-season BC changes in endurance and power event athletics competitors.